Corrugated carton flattening machine - LU JIANWU (2020)
The invention discloses a corrugated carton flattening machine. The corrugated carton flattening machine comprises a mounting seat, two groups of symmetrically-distributed supporting legs are fixedlymounted at the corners of the periphery of the top of the mounting seat, wherein each group of supporting legs involve two supporting legs, threaded holes are formed in the middles of the bottom endsof the supporting legs, mounting pieces are arranged at the bottom ends of the supporting legs, universal wheels are mounted on the mounting pieces, external threaded rods are fixedly mounted at the center positions of the tops of the mounting pieces, and the external threaded rods are in threaded connection in the threaded holes. Two groups of symmetrically-distributed supporting legs are fixedlymounted on the periphery of the bottom of the mounting seat, and each group of supporting legs involve two supporting legs so that the mounting seat can be better supported conveniently, the stability of the placement of the m